Diamonds are a Government's Best Friend: Burden-free Taxes on Goods Valued for their Values: Comment - Friedman, David D. (American Economic Review, 1988)
In a recent article (Yew-Kwang Ng, 1987), Ng demonstrates that taxes on goods whose utility is derived entirely from their market value (diamond goods) can provide revenue to the government with no cost to the taxpayers aside from the administrative costs of collecting them. Such a tax decreases the quantity of the good produced while proportionally increasing the value per unit quantity. Since the utility of the good depends only on its value, the smaller quantity produced (after the tax is imposed) produces the same total utility to consumers as the previous larger quantity. The revenue collected by the government is paid, in effect, from the reduced cost of producing a smaller quantity of the good. Ng mentions a number of earlier discussions of goods whose utility comes in part from their price. He is apparently unaware of an analysis which is both much earlier and much closer to his than any he cites. In Chapter 13 of the Principles of Political Economy, David Ricardo wrote: